In-Situ X-ray Photoelectron Spectroscopy and Raman Microscopy of Roselite Crystals, Ca2(Co2+,Mg)(AsO4)2 2H2O, from the Aghbar Mine, Morocco - Jacob Teunis Kloprogge; Barry James Wood; Danilo Octaviano Ortillo (Crystals, 2021)
Roselite from the Aghbar Mine, Morocco, [Ca2(Co2+,Mg)(AsO4)2 2H2O], was investigated by X-ray Photoelectron and Raman spectroscopy. X-ray Photoelectron Spectroscopy revealed a cobalt to magnesium ratio of 3:1. Magnesium, cobalt and calcium showed single bands associated with unique crystallographic positions. The oxygen 1s spectrum displayed two bands associated with the arsenate group and crystal water. Arsenic 3d exhibited bands with a ratio close to that of the cobalt to magnesium ratio, indicative of the local arsenic environment being sensitive to the substitution of magnesium for cobalt. The Raman arsenate symmetric and antisymmetric modes were all split with the antisymmetric modes observed around 865 and 818 cm−1, while the symmetric modes were found around 980 and 709 cm−1. An overlapping water-libration mode was observed at 709 cm−1. The region at 400–500 cm−1 showed splitting of the arsenate antisymmetric mode with bands at 499, 475, 450 and 425 cm−1. The 300–400 cm−1 region showed the corresponding symmetric bending modes at 377, 353, 336 and 304 cm−1. The bands below 300 cm−1 were assigned to lattice modes.